The Influence of Digital Leadership and Psychological Empowerment on Sustainable Employability through Work Engagement in Generation Z Employees in Bali - Ni Putu Sintya Dewi Pertiwi; Nyoman Sri Subawa; Caren Angellina Mimaki (Priviet Social Sciences Journal, 2026)
This study aims to analyze the influence of digital leadership and psychological empowerment on sustainable employability with work engagement as a mediating variable in Generation Z employees in Bali Province. This study uses a quantitative approach with a survey method of 150 respondents selected through purposive sampling techniques. Data were collected using a Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4. The results of the study show that digital leadership has a positive and significant effect on work engagement, while psychological empowerment has a significant but negative effect on work engagement. Furthermore, digital leadership does not have a significant effect directly on sustainable employability, while psychological empowerment has a significant negative effect. On the other hand, work engagement has a positive and significant effect on sustainable employability. The results of the mediation analysis show that work engagement mediates the full relationship between digital leadership and sustainable employability. Meanwhile, work engagement partially mediates the relationship between psychological empowerment and sustainable employability in a negative direction. These findings suggest that work engagement has an important role in improving the sustainability of work capacity, while the influence of leadership and psychological empowerment shows more complex dynamics in the Generation Z workforce.